Racial equity on college campuses : connecting research and practice - Johnson, Royel M.; Anya, Uju; Garces, Liliana M. (Albany : State University of New York Press, 2022)
"Offers insight into race-based disparities in higher education and practical tools for advancing racial equity on college and university campuses"--
Introduction / Royel M. Johnson, Uju Anya, and Liliana Garces -- Part 1. University Leadership. Advancing Racial Equity in Faculty Hiring through Inquiry -- Leveraging Campus-wide Leadership Collaborations for Equity -- Equity as Leadership: The Role of Boards in Achieving the Equity Agenda -- Part 2. Teaching and Learning. (Re)Shaping Higher Education Classrooms with Inclusive Pedagogies -- Developing Intersectional Consciousness: A De/colonial Approach to Researching Pedagogy in the Higher Education Context -- From the Theater to Higher Education: Using Movies to Facilitate Intergroup Racial Dialogues -- Part 3. Student and Campus Life. Reimagining Institutionalized Support for Undocumented and DACA College Students: A Critical Approach -- Rethinking Postsecondary Education Access and Success to Advance Racial Equity for Rural Black Students -- Beyond "Woke Play": Challenging Performative Allyship in Student Affairs' "Diversity, Equity, and Inclusion" Programming.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 15, 2022).
eBooks on EBSCOhost
Keywords: Racial justice in education -- United States; Discrimination in higher education -- United States; Educational equalization -- United States; Minorities -- Education (Higher) -- United States; Minority college students -- United States; Discrimination dans l'enseignement supérieur -- États-Unis.; Démocratisation de l'enseignement -- États-Unis.; Minorités -- Enseignement supérieur -- États-Unis.; Étudiants issus des minorités -- États-Unis.; EDUCATION / Higher; Discrimination in higher education; Educational equalization; Minorities -- Education (Higher); Minority college students; Racial justice in education; United States; Essays